Effects of endurance training and acute doxorubicin treatment on rat heart mitochondrial alterations induced by in vitro anoxia-reoxygenation - Ascensão, António (2006)
Abstract Endurance training (ET) and adriamycin (ADR) treatment are two conditions that have been described as triggering metabolic alterations within the myocardium. ADR is an anti-neoplastic agent with notorious cardiotoxicity, most likely because it increases oxidative stress. ET and/or ADR treatment can induce metabolic and signaling alterations affording cross-tolerance against several insults such as ischemia and reperfusion. The objective of the present work was to investigate whether heart mitochondria isolated from rats submitted to ET with or without ADR treatment were more or less susceptible to in vitro anoxia-reoxygenation (AR) when compared with control rats. Twenty-four male Wistar rats were assigned into four groups (n=6 each): control (C), ADR (20 mg-kg-1), 14 wk ET (T), and T+ADR. Respiratory parameters and oxidative damage were determined before and after 1 min anoxia followed by 4 min reoxygenation. Basal heat shock proteins (HSPs)60 and-70 and antioxidant enzymes' activity were measured. ADR by itself decreased state 3 and respiratory control ratio (RCR), as opposed to ET by itself, which improved state 3 and RCR. As expected, AR impaired state 3 and 4, RCR, and ADP/O in the C group (p>0.05). In the ADR group, AR did not induce any alteration in RCR and in ADP/O values. ET in the absence of ADR treatment prevented the impairment in RCR and ADP/O and in state 4 induced by AR. Also, despite the fact that state 3 respiration after AR was lower in all groups, it was significantly higher in the T than in the C group. Increased mitochondrial carbonyls and malondialdehyde (MDA) after AR were only found in the C group. Also, following AR, both carbonyls and MDA levels were lower in the T and in the T+ADR than in C and ADR groups, respectively. HSP60 levels were higher in the ADR, T, and T+ADR than in the C group (2.5-fold, 2-fold, and 1.9-fold increase, respectively). HSP70 increased twofold in the T and T+ADR groups. ET augmented 1.5-fold the activity of superoxide dismutase. The present work demonstrates that both ET and ADR treatment induced myocardial alterations that interfere with in vitro mitochondrial responses to AR.